Individual needs, cooperative learning and academic achievement among university’s students - Md Daud Ismail,; Mohd Zaid Razali,; Syed Shah Alam, (Pusat Pembangunan Mahasiswa dan Perhubungan Alumni, Universiti Kebangsaan Malaysia, 2015)
Academic achievement is an important indicator of student performance in institution of higher learning. Notwithstanding the intensity of investigation on academic performance, the dynamic nature of external environments engender continuous development of teaching and learning in higher learning institutions so as to minimize knowledge asymmetry. Previous studies emphasize on the important of individual needs and cooperative learning on the performance output of students of higher institution. Specifically this study investigates the role of student’s individual needs and cooperative learning on academic performance. Data was collected from 100 undergraduate students at the Universiti Kebangsaan Malaysia. Multiple regression analysis was employed to test the hypotheses. Findings indicate that individual needs significantly influences academic performance. In addition, cooperative learning mediates the relationship between individual needs and academic achievement, hence partial mediating function of cooperative learning. At the end of this paper, the discussion is presented and the conclusion is discussed.